2011
DOI: 10.1111/j.1095-8649.2011.03136.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among native trout Salmo trutta populations from southern Balkans based on mitochondrial DNA and microsatellite variation

Abstract: The genetic structure and the phylogenetic relationships among five Balkan populations of trout Salmo trutta that have been classified earlier into five different taxa were studied, using microsatellite and mitochondrial DNA (mtDNA) analyses. The pattern of population differentiation observed at microsatellites differed to that depicted by mtDNA variation, yet both methods indicated a very strong partitioning of the genetic variation among sampling locations. Results thus suggest that conservation strategies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Our analyses on populations of eastern Balkans generated considerably different results. The F ST values were significant but substantially lower compared to the values published for the Greek populations (Apostolidis et al 2008b(Apostolidis et al , 2011. Whereas the Greek populations were often fixed for one allele at several microsatellite loci, at least two alleles were found at each locus in all populations from the eastern Balkans.…”
Section: Mediterranean Basincontrasting
confidence: 70%
See 1 more Smart Citation
“…Our analyses on populations of eastern Balkans generated considerably different results. The F ST values were significant but substantially lower compared to the values published for the Greek populations (Apostolidis et al 2008b(Apostolidis et al , 2011. Whereas the Greek populations were often fixed for one allele at several microsatellite loci, at least two alleles were found at each locus in all populations from the eastern Balkans.…”
Section: Mediterranean Basincontrasting
confidence: 70%
“…Shorter sequences of the control region corresponding to ADcs1 were found in some drainages of Ionian Sea basin, Aegean Sea basin and Lake Prespa (Apostolidis et al 1997(Apostolidis et al , 2011Marić et al 2006;Snoj et al 2009). The frequency of this haplotype was very high also in the Aegean Sea basin populations analysed in this study (61% considering the Adriatic lineage only).…”
Section: Mediterranean Basinmentioning
confidence: 97%
“…According to [1] the considerable confusion regarding the taxonomy of brown trout Salmo trutta L. 1758 species complex originated from the complicated and incompletely described evolutionary history of the taxa. The situation within Salmo genus seems to be more complicated in Balkan region due to that the area hosts the most diverse phenotypic variation among Salmo spp.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, numerous Salmo taxa have been described within this important region, and it is still debatable if these taxa should be considered as phenotypic variants or true Linnean species. On the other hand, it is well established that the use of molecular markers can provide clues regarding the evolutionary origin and useful tools for the conservation and management of populations and species [1]. Following different approaches and survey in regard to Salmo spp., population with analyses and application of allozymic loci, mitochondrial (mt) DNA and microsatellites, it has been concluded that Balkan area constitute a region where Salmo spp.…”
Section: Introductionmentioning
confidence: 99%
“…They are applied for maternal traits whereas paternal traits are related to nuclear genomics. Mitochondrial genomics are genetically highly divergent indicating that they may represent distinct and potentially locally adapted gene pools (Apostolidis et al 2011). Previous researches have studied the evolutionary history of the salmo taxa species including brown trout, s. salar, and s. trutta populations (Nei 1987;Bernatchez and Wilson 1998;Avise 2000;Osinov and Lebedev 2000;Kottelat and Freyhof 2007).…”
mentioning
confidence: 99%